The Relationship Between Infant Formula and the Incidence of Dental Caries Among Stunted Children in Muaro Jambi Regency, 2024 - Gumilar, Mira Sri; Wilia Putra, Andre (Jurnal Kesehatan Gigi, 2025)
Stunting is the most prevalent form of malnutrition, with far-reaching impacts beyond just height and academic performance, as it is also associated with poor oral health conditions. A study has shown that stunted children have a high prevalence of dental caries, with a def-t index value of 53.3%. Muaro Jambi Regency has a stunting prevalence rate higher than the provincial average of Jambi, standing at 18.6%. This study aims to identify the relationship between formula feeding and the incidence of dental caries in Muaro Jambi Regency in 2024. This study employs a cross-sectional design. The sample consists of stunted children aged 1-5 years. Data analysis includes univariate, bivariate, and multivariate analyses. The results of this study show that formula feeding has a significant association with the incidence of dental caries in stunted children, with a p-value of 0.007 after controlling for the variables of cariogenic food consumption and tooth brushing habits. Furthermore, the results indicate that stunted children who are fed formula are 14.545 times more likely to develop dental caries compared to those who are not fed formula.